Dental Injuries and Management - Reddy, Likith V.; Bhattacharjee, Ritesh; Misch, Emily; Sokoya, Mofiyinfolu; Ducic, Yadranko (Facial Plastic Surgery, 2019)
Traumatic dental injuries affect 1 to 3% of the population, and disproportionately affect children and adolescents. The management of these injuries incorporates the age of patients, as children between 6 and 13 years of age have a mixed dentition. This helps to preserve the vitality of teeth that may be salvaged after a traumatic event. The clinical examination of these cases involves a thorough examination of the maxilla and mandible for associated fractures and any lodged debris and dislodged teeth or tooth fragments. The objective is to rule out any accidental aspiration or displacement into the nose, sinuses, or soft tissue. After ruling out any complications, the focus is on determining the type of injury to the tooth or teeth involved. These include clinical examination for any color change in the teeth, mobility testing, and testing for pulp vitality. Radiographic evaluation using periapical, occlusal, panoramic radiographs, and cone beam computed tomography is performed to view the effect of trauma on the tooth, root, periodontal ligament, and adjoining bone. The most commonly used classification system for dental trauma is Andreasen's classification and is applied to both deciduous and permanent teeth. Managing dental trauma is based on the type of injury, such as hard tissue and pulp injuries, injuries to periodontal tissue, injuries of the supporting bone, and injuries of the gingiva and oral mucosa. Hard-tissue injuries without the involvement of the pulp typically require restoration only. Any pulp involvement may require endodontic treatment. Fractures involving the alveolar bone or luxation of the tooth require stabilization which is typically achieved with flexible splints. The most common procedures employed in managing dental injuries include root canal/endodontics, surgical tooth repositioning, and flexible splinting. Recognition and treatment of these injuries are necessary to facilitate proper healing and salvage of a patient's natural dentition, reducing future complications to patients.
Keywords: trauma; tooth; luxation; fracture